Experimental Study on Dynamic Exhaust Law for Ventilation System of Gas Tunnel - Ping Zhang; Hui-Qing Lan (Applied Sciences, 2023)
The ventilation system is the only channel for gas exchange inside and outside the gas tunnel, which determines whether the high-risk gas in the tunnel can be exhausted in time after a gas leakage accident; thus, it is essential to study the dynamic ventilation characteristics. A fire-retarding division of the gas tunnel in Songjiang District of Shanghai is taken as the study object, and, based on the similarity theory, a similarity experiment platform is built. The simulation experiments of exhaust are carried out under different exhaust velocities, ventilation equivalent diameters and initial gas concentrations by using the control variable method. The changes in ventilation duration and gas concentration are analyzed in detail. The conclusions are as follows: (1) Time–concentration curves at all positions in the gas tunnel exhibit an “asymptote” distribution. (2) Average gas concentration has a linear relationship with time at the beginning and becomes an exponential relationship after a certain time. (3) When the exhaust velocity is 5 m/s, the initial gas concentration is 15%VOL; when the equivalent diameter of the vent in the model is 0.2 m, the ventilation duration is 100.2 s. A calculation model of ventilation duration for the standard gas tunnel is established, and the application limits of the model are 1 ≤ v ≤ 5, 0.5 ≤ d ≤ 1.5, and 5 ≤ <semantics>φo</semantics> ≤ 25. (4) In practical engineering, an exhaust velocity of 5 m/s and an equivalent ventilation diameter of 1 m are relatively optimal ventilation parameters.